2002
DOI: 10.1046/j.1365-2672.2002.01663.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of pathogenic vibrios in coastal areas of France

Abstract: Aims: This study was carried out to investigate the occurrence of potentially pathogenic species of Vibrio in French marine and estuarine environments. Methods and Results: Samples of coastal waters and mussels collected between July and September 1999 were analysed by culture, using selective media including thiosulphate-citratebile salts-sucrose and modified cellobiose-polymixin B-colistin agar. Presumptive Vibrio colonies were isolated and identified using selected biochemical tests. Specific primers based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
109
4
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(135 citation statements)
references
References 37 publications
15
109
4
7
Order By: Relevance
“…This suggests that the ratio observed here is realistic, although more strains need to be checked for more reliable evidence. Presence of the trh gene alone seems to be a common characteristic of V. parahaemolyticus communities in Northern European waters and has been shown for several studies in this region [39,69,70]. Up to now, only tdh-positive strains were associated with V. parahaemolyticus infections in Europe, however [68], and tdh is the gene that has been mainly attributed to haemolysis [71].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that the ratio observed here is realistic, although more strains need to be checked for more reliable evidence. Presence of the trh gene alone seems to be a common characteristic of V. parahaemolyticus communities in Northern European waters and has been shown for several studies in this region [39,69,70]. Up to now, only tdh-positive strains were associated with V. parahaemolyticus infections in Europe, however [68], and tdh is the gene that has been mainly attributed to haemolysis [71].…”
Section: Discussionmentioning
confidence: 99%
“…The potential health risk by this organism needs to be properly determined, especially during the summertime. The haemolysis gene vvh has been associated with a large proportion of V. vulnificus isolates in Northern European Waters [37,39] and was even used as a species-specific marker [74], suggesting that environmental V. vulnificus isolates inherently carry haemolysis genes. Despite this, V. vulnificus is generally not very virulent; however, it has an exceptional toxicity with 30 % of wound infections ending in fatalities [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 1980s few gastroenteritis cases were reported from the KP negative V. parahaemolyticus isolates, which led to the discovery of the thermostabele direct haemolysin (TDH)-related haemolysin, TRH (Hervio-Heath et al 2002). Studies revealed the TDH and TRH, encoded by the phenotypic tests viz., KP and urea hydrolysis respectively, were considered as phenotypic markers for pathogenicity (Kaysner et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies revealed an association between the Kanagawa positive phenomenon (KP+) and gastroenteritis (Okuda et al 1997a). In the 1980s few gastroenteritis cases were reported from the KP negative V. parahaemolyticus isolates, which led to the discovery of the TDH-related haemolysin (TRH) (Hervio-Heath et al 2002). Studies revealed the thermostable direct haemolysin (TDH) and the TDH-related haemolysin (TRH), encoded by the tdh and trh genes, respectively, as the major virulence factors of this organism (Shirai et al 1990).…”
Section: Introductionmentioning
confidence: 99%